Estrategias Pedagogicas Estandarizadas De Los Textos Del Ministerio De Educacion Y Su Repercusion En Los Estilos De Aprendizaje De Los Estudiantes De La Escuela Cuatro De Mayo Del Canton Babahoyo De La Provincia De Los Rios. - Cedeño Nicola, Carmen L. (2015)
The present investigation it conducted with students in the sixth year of the Education Unit May Fourth Babahoyo city, Los Rios province, investigating the impact of standardized textbooks that gives students the Ministry of Education, during the period 2013 the objectives were to verify whether teachers are prepared to understand and conduct educational activities proposed and standardized texts that delivers the Ministry of Education to students in Basic General Education May Fourth Babahoyo canton. Evaluating the effectiveness of using standardized textbooks on performance and motivation of students. We found that if teachers used the materials texts issued by the Ministry of Education, these materials accompanying teachers from other texts or materials, do so because they consider useful to incorporate additional material, consider the texts of the Ministry of Education as a complement to their teaching, students are divided some say its discretion agree and another quantity disagree with the treatment given to the textbooks issued by the Ministry of Education. The amount of activities presented in each unit texts distributed by the Ministry of Education, students disagree, because the teacher does not prepare the use thereof.